The INTEGRATION OF RELIGION-SCIENCE IN THE PERSPECTIVE OF THE QURAN: INTEGRASI AGAMA-SAINS DALAM PERSPEKTIF AL-QUR’AN - Firani Putri; Wedra Aprison (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2023)
The Qur'an instructs humans develop knowledge to thinking about how heavens earth, observe, and research the universe. The Qur'an challenges humans examine the universe down to its smallest detail. This Qur'an paradigm clearly gives birth to normative premises which can be formulated into empirical and rational theories based on general knowledge (science). The views of some people still think that science and religion stand in their respective positions, because the field of science relies on empirical data, while religion relies on doctrines that are occult. The solution to the above phenomenon is by integrating Islamic knowledge based on the Qur'an. The problem is how is the integration between science and religion in the view of the Qur'an? And what kind of integration can be between religion and science? This research is an exploratory research using a qualitative approach with research of references from journals and scientific works.The Qur'an has created this climate making knowledge a central form of Muslim consciousness, which mediates between faith and charity. The approach in integrating Islamic religious knowledge with general knowledge (science) is an integrative-interconnective approach whereby religious and scientific knowledge process of objectification where non-Muslims perceive this knowledge as appropriately, not as religious act.